Ammonium chloride as an alternative source of nitrogen for sugarcane during two consecutive cycles - Megda, Michele Xavier Vieira; Mariano, Eduardo; Leite, José Marcos; Megda, Marcio Mahmoud; Trivelin, Paulo Cesar Ocheuze (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to evaluate the effect of the application of ammonium chloride as a nitrogen source for sugarcane (Saccharum sp.) on the development of the crop’s shoot and roots during two consecutive cycles. The experiment was conducted on a Typic Hapludox in the first and second sugarcane ratoons. The treatments consisted of four N doses (50, 100, 150, and 200 kg ha-1) applied as ammonium chloride (NH4Cl), besides a control, without the application of N. The increase in the NH4Cl dose increased in up to three times soil electrical conductivity in the layer of 0.0–0.2 m, with a consequent increase in the concentration of chlorine in leaves. In the second cycle, the contents of chlorine increased in 1,900 mg kg-1 in the leaf with the application of 200 mg kg-1 NH4Cl, when compared with the control. In the first cycle, the application of NH4Cl doses above 200 kg ha-1 N promoted a decrease in shoot productivity. In both cycles, there was no effect of the NH4Cl doses on root dry matter. High doses of NH4Cl, in consecutive sugarcane cycles, result in a decrease in the productivity of stalks for processing.
Keywords: Saccharum; electrical conductivity; nitrogen fertilization; root system; stalk productivity